2013
DOI: 10.1021/ja4059876
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Basis of Serine Palmitoyltransferase Inhibition by Myriocin

Abstract: Sphingolipids (SLs) are essential components of cellular membranes formed from the condensation of L-serine and a long-chain acyl thioester. This first step is catalyzed by the pyridoxal-5'-phosphate (PLP)-dependent enzyme serine palmitoyltransferase (SPT) which is a promising therapeutic target. The fungal natural product myriocin is a potent inhibitor of SPT and is widely used to block SL biosynthesis despite a lack of a detailed understanding of its molecular mechanism. By combining spectroscopy, mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 54 publications
2
111
1
1
Order By: Relevance
“…Despite Myr treatment SPT expression was equal in both HFD and HFD/Myr animals. Myriocin acts as suicide inhibitor of SPT by covalent modification of essential catalytic serine, thus does not affect SPT expression but completely bocks its enzymatic activity at low nanomolar concentrations [54].…”
Section: Discussionmentioning
confidence: 99%
“…Despite Myr treatment SPT expression was equal in both HFD and HFD/Myr animals. Myriocin acts as suicide inhibitor of SPT by covalent modification of essential catalytic serine, thus does not affect SPT expression but completely bocks its enzymatic activity at low nanomolar concentrations [54].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the Orm proteins in regulation of SPT was first reported in an elegant study by Breslow and colleagues who showed that the Orms inhibit SPT when the cells have sufficient levels of SL [20], and the lack of Orms significantly increased he activity of SPT of six folds. When sphingolipid synthesis is disrupted by myriocin, an inhibitor of SPT activity [21], the Orms are phosphorylated at multiple sites and the inhibitory brake on SPT is relieved. As predicted, deletion or phosphomimicking mutations in the ORMs cause hyperactivation of SPT [20].…”
Section: Regulatory Mechanisms Of Sptmentioning
confidence: 99%
“…Then, the co-complex degrades via an unexpected 'retro-aldol-like' cleavage mechanism to a long chain aldehyde which, in turn, irreversibly reacts with the key catalytic residue Lys265, acting as a "suicide inhibitor" of SPT (Wadsworth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%